Pnictide-based colloidal quantum dots for infrared sensing applications - Jaeyoung Seo; Seongchan Kim; Dongjoon Yeo; Namyoung Gwak; Nuri Oh (Nano Convergence)
Abstract Pnictide-based quantum dots (QDs) have emerged as promising materials for next-generation infrared photodetectors due to their superior physical and electrical properties. Among them, InAs and InSb QDs are particularly attractive for their tunable bandgaps in the short-wave infrared (SWIR) region, high carrier mobility, and compatibility with solution-based, large-area, and low-cost fabrication processes. This review discusses recent advancements in the synthesis of InAs and InSb QDs, focusing on precursor strategies and surface engineering techniques to enhance their optical and electronic properties. Additionally, we explore their integration into infrared photodetectors, analyzing current performance and limitations. Finally, we outline future research directions aimed at further enhancing material properties and device performance, paving the way for the broader adoption of III–V QDs in next-generation infrared technologies. Graphical Abstract